Plasmodium falciparum parasite population structure and gene flow associated to anti-malarial drugs resistance in Cambodia. (December 2016) - Dwivedi, Ankit; Khim, Nimol; Reynes, Christelle; Ravel, Patrice; Ma, Laurence; Tichit, Magali; Bourchier, Christiane; Kim, Saorin; Dourng, Dany; Khean, Chanra; Chim, Pheaktra; Siv, Sovannaroth; et al.
Abstract Background Western Cambodia is recognized as the epicentre of emergence ofPlasmodium falciparum multi-drug resistance. The emergence of artemisinin resistance has been observed in this area since 2008–2009 and molecular signatures associated to artemisinin resistance have been characterized ink13 gene. At present, one of the major threats faced, is the possible spread of Asian artemisinin resistant parasites over the world threatening millions of people and jeopardizing malaria elimination programme efforts. To anticipate the diffusion of artemisinin resistance, the identification of theP. falciparum population structure and the gene flow among the parasite population in Cambodia are essential. Methods To this end, a mid-throughput PCR-LDR-FMA approach based on LUMINEX technology was developed to screen for genetic barcode in 533 blood samples collected in 2010–2011 from 16 health centres in malaria endemics areas in Cambodia. Results Based on successful typing of 282 samples, subpopulations were characterized along the borders of the country. Each 11-loci barcode provides evidence supporting allele distribution gradient related to subpopulations and gene flow. The 11-loci barcode successfully identifies recently emerging parasite subpopulations in western Cambodia that are associated with the C580Y dominant allele for artemisinin resistance ink13 gene. A subpopulation was identified in northern Cambodia that was associated to artemisinin (R539T resistant allele ofk13 gene) and mefloquine resistance. Conclusions The gene flow between these subpopulations might have driven the spread of artemisinin resistance over Cambodia.